Successful traction of a mesially 90° dilacerated root of impacted maxillary canine: A case report - Fani Tuti Handayani; Ida Ayu Evangelina (Dental Journal, 2022)
Background: Impacted maxillary anterior teeth are a problem that has a significant impact on the aesthetics of the smile, dental arches, and occlusion. Teeth that have higher tendencies to get impacted are third molars, maxillary central incisors, maxillary canines, and mandibular premolars. Impacted teeth with severe root dilacerations are usually extracted surgically, then the space will be closed by orthodontic treatment or using a prosthesis. Purpose: This study aims to report the successful orthodontic traction of mesially 90° dilacerated root of impacted maxillary canine. Case: A 15-year-old female patient with the chief complaint of an unerupted left maxillary canine. Intraoral examination showed a class I molar relationship on both sides, a unilateral crossbite on the right side, 8 mm spacing between the maxillary left lateral incisor and the premolar. Also, mild crowding was found on both upper and lower anterior segments. CBCT results showed a left maxillary canine was palatally semi-vertical impacted and had a mesially 90° dilacerated root. A significant stress concentration occurred at the middle and apical of the dilacerated root apex when exposed to orthodontic force; this tends to be a higher potential for resorption. Case Management: The impacted dilacerated canine was successfully moved to the proper position by combining crown exposure surgery, orthodontic traction using continuous light force, and gingivectomy. Furthermore, traction was held using a gold chain combined with an elastic thread tied initially to a modified stainless-steel main archwire; this was followed by piggyback tandem wire and a vertical 3/16” light elastic traction. Conclusion: The patient showed successful traction of the canine in less than six months. In addition, the unilateral posterior crossbite was corrected and functional occlusion was achieved. That canine showed good orthodontic and periodontal stability at one-year follow-up, without any evidence of root resorption.